2017
DOI: 10.1371/journal.pone.0172252
|View full text |Cite
|
Sign up to set email alerts
|

TMG-123, a novel glucokinase activator, exerts durable effects on hyperglycemia without increasing triglyceride in diabetic animal models

Abstract: Glucokinase (GK) plays a critical role for maintaining glucose homeostasis with regulating glucose uptake in liver and insulin secretion in pancreas. GK activators have been reported to decrease blood glucose levels in patients with type 2 diabetes mellitus. However, clinical development of GK activators has failed due to the loss of glucose-lowering effects and increased plasma triglyceride levels after chronic treatment. Here, we generated a novel GK activator, TMG-123, examined its in vitro and in vivo phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…10 It has also been known that pharmacological activation of hepatic glucokinase increases hepatic glucose uptake by enhancing the first metabolic reaction of glycolysis. 7 In our liver perfusion study, we showed that hepatic glucose production in Goto-Kakizaki rats was higher compared to Wistar rats and the administration of GKA increased hepatic glucose uptake. These results were consistent with previous reports, and therefore, we considered that our method can evaluate physiological responses of hepatic glucose metabolism correctly.…”
Section: Pathophysiological and Pharmacological Analyses Using The Prmentioning
confidence: 65%
See 1 more Smart Citation
“…10 It has also been known that pharmacological activation of hepatic glucokinase increases hepatic glucose uptake by enhancing the first metabolic reaction of glycolysis. 7 In our liver perfusion study, we showed that hepatic glucose production in Goto-Kakizaki rats was higher compared to Wistar rats and the administration of GKA increased hepatic glucose uptake. These results were consistent with previous reports, and therefore, we considered that our method can evaluate physiological responses of hepatic glucose metabolism correctly.…”
Section: Pathophysiological and Pharmacological Analyses Using The Prmentioning
confidence: 65%
“…TMG-123, a GKA, was synthesized in Teijin Pharma Limited (Tokyo, Japan). 7 All other reagents were analytical grade. Ultrapure water purified by a Milli-Q Integral 10 system (Merck Millipore, MA) was used throughout the study.…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…Some agents like AZD6370, piragliatin, DS-7309, and ARRY-403 also terminated their drug development due to toxicity and loose of effectiveness with long-term administration. [47][48][49][50][51] Some examples of the GK activator presented in Table 3 with their stage of development and company.…”
Section: Dovepressmentioning
confidence: 99%
“…These samples are analyzed with regard to glucose and insulin to generate dynamic profiles in the absence and presence of the study compound. Preclinically, the glucose protocols differ slightly from other glucose administrations (e.g., intraperitoneal), different duration of, or no, fasting prior to glucose challenge, but, most importantly, sometimes only measuring glucose …”
mentioning
confidence: 99%
“…Preclinically, the glucose protocols differ slightly from other glucose administrations (e.g., intraperitoneal), different duration of, or no, fasting prior to glucose challenge, but, most importantly, sometimes only measuring glucose. [6][7][8] Pharmacometric analysis based on time-course data is increasingly used in drug development, due to its integrative nature and the ease with which it can handle dynamic relationships. [9][10][11] There are several examples in which pharmacometric analysis has been shown to be highly powerful in phase II trials.…”
mentioning
confidence: 99%